Desperate Housewives : The Complete Second Series Disc 2 Episodes 5-8 - John, David G., 1947-; Hatcher, Teri. (USA Buena Vista Home Entertainment, 2004)
In its first season, the show reveals the mystery of why Mary Alice took her own life and the quest by a mysterious "plumber" named Mike Delfino (James Denton) to find out the fate of his former lover, drug addict Dierdre. By the end of the season, the show resolves the mystery with the revelation that 15 years ago, when Mary Alice's name was Angela Forrest, she buys the heroin-addicted Dierdre's only son Dana, and then flees with her husband Todd (now Paul) to Fairview (the town Housewives is set in) to keep the child (now named Zach) from being taken away from them. When Dierdre finds them, Mary Alice refuses to give up the child. Upon being accused of being back on drugs, Dierdre hits Paul (Mary Alice's husband) and goes to get her son. Mary Alice, shocked, murders her, checks her arm for signs of drug use (she was not), and has her horrified husband dismember the body, put it in Zach's toy-chest, and bury it where the family is building a new pool in their backyard. All this happens while a 4-year-old Zach is watching them from the staircase. What Mary Alice does not count on is that one of her neighbors, Martha Huber, learns of Mary Alice's secret from her sister, Felicia, (with whom Mary Alice had worked before coming to Fairview). After learning the secret, Martha attempts to blackmail Mary Alice. Rather than face the blackmail, Mary Alice kills herself. Later, when Paul finds this out, he kills Martha after she tells him she does not have any regrets about her blackmailing and its result. Mike (Dierdre's former lover) learns of this information from Paul whom Mike leaves in the desert (rather than killing) after Mike realizes that Zach is his son.
Time to come clean
Language : English Subtitle : English
Keywords: Comedy; Drama; Mystery; Romance -- Tv Series